If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(bx + -1c) = d (bx * a + -1c * a) = d (abx + -1ac) = d Solving abx + -1ac = d Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Combine like terms: d + -1d = 0 abx + -1ac + -1d = 0 The solution to this equation could not be determined.
| .2x^2-9x+5000= | | 25X^8-x^6=0 | | w^3-5w^2+7w-35=0 | | -5(2-7h)=12-3(15h+5) | | (x-6)+2(2x+4)=0 | | w^2+9w+5w+45=0 | | w(w+1)+9(w+1)=0 | | 7v^2-42=32v | | 211-k/3=111 | | 10x=2x+.5(60) | | 7(2-4y)=42 | | 20x-28=10x+2 | | 8y+2y=30 | | 2x^6-4x^5+14x^4= | | 144=(x+2)(x)(6) | | 18w^12+12w^10=0 | | 0.6-15=1x+9 | | 10+4x+20=-6x+10 | | 0.66666666x-15=1x+9 | | 2x^5+6x^4+14x^3=0 | | -3x+7=17 | | 7/9-d=1/3 | | 2x-6=8x+10 | | 4x+6y+62-6x+6y+-18= | | -9(0.25)+6-(0.25)=4 | | -y-[6(y-1)-2(3+y)]=3(4-y)-2y | | 92-14=-45 | | 17=4y+8-7y | | 2x+3.6=x+2.8 | | 0.3x+21=-0.7x+8 | | 24x^2y-42xy+9y=0 | | 11x+-6=17 |